Cross-Border Portfolio Flows and News Media Coverage - Guglielmo Maria Caporale; Faek Menla Ali; Fabio Spagnolo; Nicola Spagnolo (Center for Economic Studies and ifo Institute (CESifo), 2020)
This paper investigates the dynamic linkages between portfolio flows and various news indices (based on both "positive" and "negative" news headlines collected from Bloomberg), whilst also controlling for a comprehensive set of push and pull factors. The monthly panel examined comprises 49 developed and developing countries in addition to the US (the "home economy") and covers the period from January 2007 to October 2017; the econometric model includes fixed effects. The empirical results document the important role played by the news variables. More specifically, news pessimism and intensity affect bond flows more than equity flows, and US news appears to play a leading role in these portfolio flow dynamics. By contrast, changes in news pessimism and intensity have a more significant impact on equity flows, and again US news tend to have more sizeable effects. News sentiment is generally found to be an important driver of portfolio flows, whilst only US news disagreement has a significant effect, and only on bond inflows into the US. Most results are robust to the exclusion of the six financial centres from the full sample. As for push and pull factors, most of them (equity return differentials, interest rate spreads, the VIX index, capital controls, exchange rate regimes, CDS spreads, QE episodes, financial development and commodity prices) are significant and with the expected signs.
Keywords: F31; F32; G15; 330; Bloomberg; bond flows; equity flows; news